PENGARUH MADU TERHADAP KARAKTERISTIK FISIK, KIMIA, DAN MIKROBIOLOGI VELVA JAMBU BIJI MERAH (Psidium guajava L.) PROBIOTIK (Lactobacillus acidophilus IFO 13951) - Mandasia Pangastuti; Dwi Ishartani; Rohula Utami; M. Zukhrufuz Zaman (Agroindustrial Technology, University of Trunojoyo Madura, 2020)
This study was processed pink guava becomes probiotic’s velva as a functional food which safe to be consumed by lactose intolerance. The use of honey as a substitute for sucrose is expected to minimize calorie content, increase functional value, and maintain the viability of LAB in velva. The aim of this study was to determine the effect of honey on velva’s characteristics (total soluble solids, overruns, melting rate, and total calories), to determine the effect of honey on velva’s characteristics (pH, titratable acidity, and total LAB) during storage, and to determine the effect of honey on velva’s vitamin C levels and antioxidant activity after 6 weeks storage. There were 4 treatments which consist of F0 25% sucrose (control), F1 15% honey, F2 20% honey, and F3 25% honey. This study used Randomized Block Design. Data was analyzed using One Way ANOVA. The results showed that variations in honey concentrations significantly affect the characteristics of the velva (total soluble solids, overruns, melting rate, and total calories), affecting the pH value and total LAB during storage, and affecting vitamin C levels and antioxidant activity after storage. The higher the concentration of honey, the higher the value of total soluble solids, melting rate, total calories, vitamin C levels, antioxidant activities, and was effective at preserving the viability of LAB, while the value of overrun, and pH is lower.